Effect of Protamex Hydrolysis on Foaming Properties and Structural Properties of Corn Glutelin - FAN Guangqi, WANG Juntong, LI Dan, CUI Suping, LI Jing, ZHENG Xiqun (Shipin Kexue, 2023)
The effects of different durations of hydrolysis with Protemex on the foaming properties, surface tension, physicochemical properties and static rheological properties of corn glutelin were determined. The results showed that the solubility and foaming properties of corn glutelin were significantly improved by Protamex hydrolysis. The foaming capacity of the 120 min hydrolysate was highest, which was 2.8 times higher than that of corn glutelin, and its foam stability was also good. The hydrolysate had the lowest surface tension and the highest apparent viscosity. The microscopic morphology of the foam formed was fine and uniform, with a thick protein film. With the prolongation of hydrolysis time, the average particle size of corn glutelin hydrolysates decreased continuously, the endogenous fluorescence intensity and surface hydrophobicity increased gradually, while the surface net charge decreased first and then increased. The results of Raman spectroscopy showed that after appropriate hydrolysis, the α-helix content decreased, and the random coil and β-angle contents increased; the peak intensity ratio of tyrosine residues (I850/I830) increased, and the peak intensity of tryptophan residues (I760) decreased. Nevertheless, the β-folding content changed little. Long-time hydrolysis significantly increased the content of random coil and decreased the peak intensity ratio of tyrosine residues (I850/I830). Therefore, restricted hydrolysis can change the structure and interface properties of corn glutelin, improve its foam properties, and consequently increase the potential utilization rate of corn gluten meal in the food field.